KONSEP MODERASI BERAGAMA DALAM PENAFSIRAN QS. AL-BAQARAH [2]: 143 (STUDI KOMPARATIF TAFSIR IBNU KAṠIR DAN TAFSIR AL-MISBAH) - wakhidah, siti nur; Gaffar, Abdul Gaffar; Danial, Danial Danial; Rifai, Masyhuri Rifai (EL-MAQRA', 2024)
This research is about the concept of religious moderation in the interpretation of QS. AlBaqarah [2]: 143 (comparative study of Ibnu Kaṡir's tafsir and Al-Misbah's tafsiraims to describe the method of interpreting QS. Al-Baqarah [2]:143 in the tafsir of Ibn Kaṡir and M.Quraish Shihab in the tafsir of Al-Misbah. Study This aims to describe the method of interpreting QS. Al-Baqarah [2] :143 in the tafsir of Ibn Kaṡir and M. Quraish Shihab in the tafsir of Al-Misbah after that in order to analyze the relationship between QS interpretation. Al-Baqarah [2]: 143 against religious moderation in Ibn Kaṡir's tafsir and Al-Misbah's tafsir. This research is qualitative research with the type of library research (Library research). The analysis technique used is the comparative analysis method (comparison). The research results show that: first, religious moderation in QS. Al-Baqarah [2] : 143 in Ibn Kaṡir's commentary which interprets from The word Ummatan Wasathan is the best choice, from the interpretation of the word الوسط interpreted with the word حيار choice then جواداال best so is choice the best جوادَاالَخيارو while in Tafsir Al-Misbah interprets the word Ummatan Waslahan is the middle or middle way. Second, the method used in Ibn Kaṡir's tafsir in interpreting QS. Al-Baqarah [2] : 143 is tahlili with a method of interpreting pieces of verse and strengthening it with Other verses of the Qur'an and hadith, while in the interpretation of Al-Misbah interpret QS. Al-Baqarah [2] : 143 using the opinion of para scholars and the opinions of the commentators themselves. Third, in terms of style, second This interpretation has differences if Ibn Kaṡir's interpretation tends to lead to tafsir Bi al-Matsur (interpreting the Qur'an with the Qur'an, the Qur'an with hadith) while the interpretation of Al-Misbah tends to be in the Adabi Ijtima'i style (style social culture literature). These two commentators lived in different eras namely the contemporary era and the present era. The writing also has different interpretations Ibn Kaṡir was written much more than 700 years ago while Tafsir Al-Misbah written in today's era, now from here it is clear that there must be differences in era or period that influences the interpretation of each interpreter.